Global Health System Resilience during Encounters with Stressors – Lessons Learnt from Cancer Services during the COVID-19 Pandemic. Issue 4 (April 2023) - Yeoh, K.; Wu, Y.; Chakraborty, S.; Elhusseiny, G.; Gondhowiardjo, S.; Joseph, N.; Lee, A.W.M.; Loong, H.H.; Msadabwe-Chikuni, S.C.; Tan, B.F.; Ospina, A.V.; Roques, T.; et al.
Abstract: Aims: The protracted COVID-19 pandemic has overwhelmed health systems globally, including many aspects of cancer control. This has underscored the multidimensional nature of cancer control, which requires a more comprehensive approach involving taking a wider perspective of health systems. Here, we investigated aspects of health system resilience in maintaining cancer services globally during the COVID-19 pandemic. This will allow for health systems to be resilient to different types of system stressors/shocks in the future, to allow cancer care to be maintained optimally. Materials and methods: Using the World Health Organization health system framework (capturing aspects of service delivery, health workforce, information, medical products, vaccines and technologies, financing and governance and leadership), we carried out a comparative analysis of the impact of COVID-19 and the synthesis of the findings in responses in cancer care in 10 countries/jurisdictions across four continents comprising a wide diversity of health systems, geographical regions and socioeconomic status (China, Colombia, Egypt, Hong Kong SAR, Indonesia, India, Singapore, Sri Lanka, UK and Zambia). A combination of literature and document reviews and interviews with experts was used. Results: Our study revealed that: (i) underlying weaknesses of health systems before the pandemic were exacerbated by the pandemic (e.g. economic issues in low- and middle-income countries led to greater shortage of medication and resource constraints compounded by inadequacies of public financing and issues of engagement with stakeholders and leadership/governance); (ii) no universal adaptive strategies were applicable to all the systems, highlighting the need for health systems to design emergency plans based on local context; (iii) despite the many differences between health systems, common issues were identified, such as the lack of contingency plan for pandemics, inadequate financial policies for cancer patients and lack of evidence-based approaches for competing priorities of cancer care/pandemic control. Conclusion: We identified four key points/recommendations to enhance the resilient capacity of cancer care during the COVID-19 pandemic and other system stressors: (i) effective pandemic control approaches in general are essential to maintain the continuity of cancer care during the emergency health crises; (ii) strong health systems (with sufficient cancer care resources, e.g. health workforce, and universal health coverage) are fundamental to maintain quality care; (iii) the ability to develop response strategies and adapt to evolving evidence/circumstances is critical for health system resilience (including introducing systematic, consistent and evidence-based changes, national support and guidance in policy development and implementation); (iv) preparedness and contingency plans for future public health emergencies, engaging the whole of society, to achieve health system resilience for future crises and to transform healthcare delivery beyond the pandemic. Highlights: Effective containment of COVID-19 in general led to least disruption of cancer care. Pre-existing weakness of health systems was exacerbated during the pandemic. Adaptive strategies need to evolve with evidence and changing circumstances. Preparedness plans are needed for future shocks to enable systematic response. Building resilience requires both health system improvements and emergency preparedness.